2014
DOI: 10.1177/0954405414546705
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulation and experimental investigation of friction stir processing of Polyamide 6

Abstract: In this article, Deform© three-dimensional package was used to develop a numerical model for friction stir process of Polyamide 6 based on Lagrangian incremental formulation, and additional experiments were done to verify this objective. For this purpose, the friction stir process was used to disperse the multi-walled carbon nano-tubes among the polymer matrix of Polyamide 6 homogeneously. Thermo-mechanical properties, for example, effective plastic strain distribution and material flow together with temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…, comparing the cryofractured surfaces of SV 4 and SV 5 shows that very small EPDM particles are obtained when using of higher rotational speed and shear stress to produce nanocomposite. This related to the fact that the higher rotating speed in FSP lead to the higher shear stress and decreases size of elastomer particles .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, comparing the cryofractured surfaces of SV 4 and SV 5 shows that very small EPDM particles are obtained when using of higher rotational speed and shear stress to produce nanocomposite. This related to the fact that the higher rotating speed in FSP lead to the higher shear stress and decreases size of elastomer particles .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently a rotating tool is plunged into the sheet and traversed along the groove to disperse particles to the base material. The study of the literature review shows very few reports on fabricating polymeric composite and nanocomposites by FSP . For instance, enhancement of morphology and mechanical properties of polyethylene (PE)/copper composite and high density polyethylene (HDPE)/clay nanocomposite fabricated using FSP have been reported by Azarsa and Mostafapour and Barmouz et al, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the grain size of the alloy after FSP decreased significantly. Comparing the effect of variation in the parameters on various characteristics of the FSPed alloy, they observed that the increase in the number of passes (1)(2)(3) led to an increase in the mean grain size and ductility and contrarily caused a reduction in the strength and hardness. The increase in the feed rate (90-240 mm/min) led to an increase in the grain size, strength and hardness while a decrease in the ductility.…”
Section: Introductionmentioning
confidence: 97%
“…5 Because of these salient features, the process is gaining increasing popularity in the materials and manufacturing sectors. 6 FSP in the simplest form employs a non-consumable rotating tool with a specially designed pin and a shoulder as integral parts. The process starts with the plunging of pin into a monolithic workpiece.…”
Section: Introductionmentioning
confidence: 99%